PENGARUH PEMBERIAN SUSU TEMPE TERHADAP KADAR HAEMOGLOBIN PADA IBU HAMIL TRIMESTER III - Yuniwati, Yuniwati (JURNAL MEDIA KESEHATAN, 2014)
The incident of anemia in Bengkulu City was still high (around 45%) and it could be the risk factor of post partum haemorrhagic. Alternative therapeutic that can be developed was the tempe-feeding because high amino acid and vitamin of B 12 in tempe. This research caused to know influence of tempe feeding for average haemoglobin level of pregnant women in 3th semester of pregnancy at BPS Bengkulu City. The design was pre-experiment one group pre and post test, with pregnant women population in 3th semester of pregnancy at BPS Bengkulu City with samples one 12 person. The results showed average haemoglobin level to the pregnant women in 3th semester of pregnancy before intervention was 11.50 gr/dl and after tempe-feeding became 12.41 gr/dl. There was relationship between tempe-feeding to average haemoglobin level with result p=0.005 and mean difference was 0.91. There was relationship between consumption of protein and iron tablets to haemoglobin level. There was no relationship between vitamine C consumption and economic statues to haemoglobin level, tempe-feeding influenced to the improvement average haemoglobin for pregnant women 3th semester of pregnancy. Adviced to health provider to counseling about nutrition of tempe as a alternative food cheaper and high nutrition for the pregnant women.